2015
DOI: 10.3758/s13414-015-0912-7
|View full text |Cite
|
Sign up to set email alerts
|

Sleep after practice reduces the attentional blink

Abstract: The attentional blink (AB) is an impairment in detecting the second of two targets that appear in close temporal succession. We investigated the effect of practice and a nap on the magnitude of the AB deficit. We found evidence that sleep boosts practice-dependent reduction of the AB. Participants reported two target letters embedded in a rapid serial visual presentation display. After two morning sessions, half the participants took a polysomnographically recorded nap, while the others remained awake. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
5
13
0
Order By: Relevance
“…Measuring the AB effect and its training-related modulation requires comparing the accuracy at a short lag versus accuracy at a long lag 49 . Previous studies using similar RSVP stimulation as in our study showed a most pronounced AB effect at the lag of two or three (180 to 270 ms) 35,36,50 and specific effects of training were found for the target at a lag of two [51][52][53] . Therefore, we observed the T2 | T1 accuracy at a lag of two and compared this measure with the accuracy in the control condition, assuming that the accuracy in the control condition reflects the asymptotic T2 | T1 accuracy for a long lag.…”
Section: Meg Recordingssupporting
confidence: 80%
See 1 more Smart Citation
“…Measuring the AB effect and its training-related modulation requires comparing the accuracy at a short lag versus accuracy at a long lag 49 . Previous studies using similar RSVP stimulation as in our study showed a most pronounced AB effect at the lag of two or three (180 to 270 ms) 35,36,50 and specific effects of training were found for the target at a lag of two [51][52][53] . Therefore, we observed the T2 | T1 accuracy at a lag of two and compared this measure with the accuracy in the control condition, assuming that the accuracy in the control condition reflects the asymptotic T2 | T1 accuracy for a long lag.…”
Section: Meg Recordingssupporting
confidence: 80%
“…Such delayed effect is characteristic of perceptual learning requiring consolidation during sleep 67 . That sleep after training improves the AB performance has been shown previously 51 . Thus, we assume that the BB stimulation interacted with a neural network underlying learning and training rather than immediately with perception.…”
Section: Discussionsupporting
confidence: 67%
“…Indeed, when controlling for total sleep time, which was significantly associated with consolidation of unpleasant pictures presented before sleep, the correlation between memory discrimination and number of N2 spindles became non-significant. Therefore we can only speculate that sleep spindles, which are a hallmark feature of N2 sleep and were previously associated with memory , attention (Cellini, Goodbourn, McDevitt, Martini, Holcombe, & Mednick, 2015), and intelligence abilities (Fogel & Smith, 2011), may facilitate the consolidation of negative information. This result may be consistent with two recent studies reporting an association between emotional memory consolidation and sleep spindles (Cairney, et al, 2014a;Kaestner, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that distinct cognitive domains benefit from specific sleep stages and features. For example, our lab and others have shown that activity of sleep spindles (Mednick et al, 2013) and slow oscillations (SO: .5-1Hz, Rihms et al, 2014), as well spindle/SO coincidence (Niknazar et al, 2015) in a post-training sleep period correlate with the magnitude of declarative memory improvement (e.g., conscious, episodic memories), and spindles are also associated with improved attention (Cellini et al, 2015). On the other hand, minutes in REM sleep and REM theta activity (4-8Hz) correlate with improvement in non-declarative memories (e.g., unconscious, perceptual or sensorimotor skills) (Mednick, Nakayama, & Stickgold, 2003) and emotional salient memories (Groch, Wilhelm, Diekelmann, & Born, 2013;Hutchison & Rathore, 2015).…”
Section: An Introduction To Sleepmentioning
confidence: 75%